2004
DOI: 10.1159/000078499
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Bone Measurement during the 1st Trimester: Is It Useful?

Abstract: The aim of this study was to present our preliminary data about nasal bone measurements at 11–14 weeks of pregnancy. This study was conducted in our prenatal unit between 2000 and 2003. A total of 642 pregnant women (single pregnancies) were enrolled into the study. During the first trimester of pregnancy, crown-rump length, nuchal translucency thickness, and fetal nasal bone length measurements and ductus venosus Doppler images were evaluated. The distribution of absent or small nasal bones in both normal fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 18 publications
4
10
1
2
Order By: Relevance
“…However, after a sufficient period of training, they may be easily incorporated to the first-trimester screening test parameters. Moreover, fetal NBL measurements in our study were comparable to previous studies from Turkey (7,15,16) and from other ethnicities (6,17). …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, after a sufficient period of training, they may be easily incorporated to the first-trimester screening test parameters. Moreover, fetal NBL measurements in our study were comparable to previous studies from Turkey (7,15,16) and from other ethnicities (6,17). …”
Section: Discussionsupporting
confidence: 90%
“…If the NB was more echogenic and thicker than the overlying skin, it was assumed to be present. If the NB was either the same or less echogenic or it was not visualized clearly then it was assumed to be absent (6,7,8,9). The fetal NBL was measured by placing the calipers in an out-to-out position (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This retrospective study suggests that adding this fourth marker (nasal bone) improves detection of trisomy 21 and reduces the initial screen-positive rate. These results agree with other studies that have shown absent [3, 4,5 ] or hypoplastic nasal bone [6] to be a useful marker for Down syndrome.…”
Section: Nasal Bonesupporting
confidence: 93%
“…A mensuração do osso nasal nessa fase da gestação tem demonstrado reprodutibilidade inadequada 8 . Estudos prospectivos e randomizados, em populações de baixo risco, se tornam necessários para avaliar se a mensuração do comprimento do osso nasal no primeiro trimestre oferece benefício adicional além da avaliação qualitativa de sua presença ou ausência 23 . Esforços devem ser feitos para melhor padronização, treinamento e controle de qualidade para validar a medida do comprimento do osso nasal no rastreamento da síndrome de Down na população geral 8 , além de permitir comparação dos diversos trabalhos.…”
Section: Idade Gestacional (Semanas)unclassified